Pertanggungjawaban Pidana Korporasi Dalam Hukum Pidana Islam - Anggraini, Rina; Sitepu, Rajin (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Corporate criminal liability has become an important issue in modern criminal law, including in the context of Islamic criminal law. Although Islamic criminal law has historically emphasized individual liability, developments in the era require an analysis of the possibility of applying criminal liability to non-individual entities such as corporations. This article examines the concept of corporate criminal liability from the perspective of Islamic criminal law with a juridical-normative approach and comparative analysis of positive law. The results of the study show that although Islamic criminal law does not explicitly recognize the concept of corporations as subjects of criminal law, basic principles such as collective responsibility (al-mas’uliyyah al-jama’iyyah), the role of representatives in criminal acts, and justice (‘adl) can be used as a basis for building a framework for criminal liability for corporations. Thus, Islamic criminal law has the potential to accommodate corporate criminal liability through a reinterpretation of the basic principles of sharia